Molecular Identification of Fungi carried by Chili Seeds (Capsicum annuum L.) from Tanjung Morawa B Village, North Sumatra - Dewi Novina Sukapiring; Lily Novianty; Siti Nurlani Harahap (Universitas Labuhanbatu, 2024)
Seed-borne fungi are fungi that are associated with seeds and can be a source of plant disease in the field. Therefore, this study aims to utilize DNA barcoding to identify seed-borne fungi isolates from Tanjung Morawa B village. This investigation took place at Tangerang's genetic science laboratory in Tangerang was the site of this investigation. Sequence and phylogenic tree building, PCR amplification with MyTaq HS Red Mix, 2X (Bioline, BIO-25048), and genomic DNA extraction with the Quick-DNA Magbead Plus Kit (Zymo Research, D4082) were the research methods used. The electrophoresis results showed that the DNA made from PCR using Primers ITS-1 and ITS-4 was of high quality. This was clear from the electrophorograms for both the TMIE isolate sample and the control. Using ITS-1 and ITS-4 for DNA amplification produced favorable results, with virtually no smears detected. The Basic Local Alignment and Search Tool (BLAST) program, which is connected to the Genebank database, was employed to analyze the sequence results in the form of a base sequence with a length of 581 base pairs. Based on the genetic similarity results of the isolate's DNA with Genebank, we determined that the TMIE isolate was 100% similar to Curvularia eragrostidis.